2011
DOI: 10.1093/eurpub/ckr040
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a screen time-based sedentary behaviour questionnaire for adolescents: The HELENA study

Abstract: The HELENA sedentary questionnaire is reliable, yet only correctly classifies objectively measured sedentary time in boys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 19 publications
1
98
1
4
Order By: Relevance
“…In addition, food consumption and sedentary behaviours data are based on self-reported questionnaires where errors in reporting are possible; nevertheless, questionnaire use is the most common method due to low-cost and ease of administration in a large European sample, and both questionnaires have been tested and validated indicating acceptable accuracy. 20,25 In addition, food accessibility at home setting is not been addressed in the HELENA study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, food consumption and sedentary behaviours data are based on self-reported questionnaires where errors in reporting are possible; nevertheless, questionnaire use is the most common method due to low-cost and ease of administration in a large European sample, and both questionnaires have been tested and validated indicating acceptable accuracy. 20,25 In addition, food accessibility at home setting is not been addressed in the HELENA study.…”
Section: Discussionmentioning
confidence: 99%
“…For the majority of the variables, Cohen's kappa values using quadratic weights showed a good agreement (40.7). 25 …”
Section: Sedentary Behavioursmentioning
confidence: 99%
“…However, both questionnaires have been tested and validated, indicating acceptable accuracy. 32,33 Evaluation of the home environment as well as parental attitudes and practices have not been addressed in this study. Therefore, further studies are needed to assess their possible interactions with the observed findings.…”
Section: Commentmentioning
confidence: 99%
“…Previous studies have reported differences between men and women in validity findings for a sedentary behavior questionnaire, in US overweight adults [17] and in European adolescents [18]. Next to gender, other demographic factors, such as age and educational level, may also influence validity.…”
Section: Introductionmentioning
confidence: 99%